Double gloving of disposable nitrile gloves exposed to diethylene glycol mono-n-butyl ether. Issue 7 (2nd August 2020) - Takaku-Pugh, Sayaka; Que Hee, Shane
Abstract: Double gloving of disposable gloves is now commonplace in healthcare settings when extra protection is needed against aqueous solutions and especially for antineoplastic drugs in isotonic aqueous media. In the present study, an ASTM F739 2.54 cm cell with closed-loop water collection without recirculation at 35 °C in a moving tray water bath was used to test the permeation of diethylene glycol mono-n-butyl ether (DGBE) through four types of disposable nitrile gloves that were singly and doubly layered in the permeation cell. Samples were taken over 8 hr for capillary gas chromatograph-mass spectrometer quantitation. The breakthrough time (tn ) at a permeation of 250 ng/cm 2 increased as thickness increased for single layers, but the steady-state permeation rates Ps in µg/cm 2 /min did not always decrease with increasing thickness. The double-layer tn, Ps and thickness were also more variable relative to a single layer. The thinnest glove with 80  μ m thickness showed a tn = 0–5 min whereas its double layer was 15–20 min. The thickest glove of 132 µm exhibited a tn = 10–15 min but its double layer was tn = 45–55 min. The adjusted double-layer average tn divided by the adjusted single-layer average tn was 4.0 ± 0.8. The adjusted average single-layer Ps divided by the adjusted average double-layer Ps was 3.5 ± 0.8. Other results showed that the average glove swelling was <10%; microscopic and leak testing indicated no penetration and reflectance infrared analysis also showed no chemical changes on the inside glove surfaces. Thus, the permeations were adjudged to obey Fick's First Law of Diffusion to allow calculation of diffusion coefficients D in cm 2 /min. The average single-layer D divided by the average double-layer D was 1.3 ± 0.2. Double gloving in the field is therefore also probably more protective than single gloving against DGBE for the four types of disposable nitrile gloves tested.